Day 3 Thu, October 31, 2019 2019
DOI: 10.4043/29885-ms
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Mechanisms of Low-Salinity Water Injection EOR Processes: A Molecular Simulation Viewpoint

Abstract: In this work, we present a multiscale approach based on first-principles calculations and classical molecular dynamics methods, to investigate the enhanced oil recovery via low-salinity water injection (EOR-LSWI). Salting-in effect, wettability, pH alteration, electrical double layer and the main geochemical reactions involved in the multicomponent ionic exchanges mechanism were analyzed in order to understand their contribution, also to provide an overall phenomenological perspective of the involved phenomena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was found that precipitated asphaltene molecules on the rock surface can be adsorbed in nanofluids containing metal oxide nanoparticles, such as TiO 2 , SiO 2 and Fe 2 O 3 [30,37,38]. Other experimental and modeling studies have revealed that the injection of modified brine during the EOR process could desorb asphaltene molecules and other polar components of crude oil from the mineral surfaces and alter the wettability of the pore wall to less oil wet, resulting in improved oil recovery [7,[39][40][41][42]. Ligthelm et al showed that a decrease in salinity increased the expansion of the diffuse double layer between the rock and oil interfaces, facilitating the release of organic materials [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that precipitated asphaltene molecules on the rock surface can be adsorbed in nanofluids containing metal oxide nanoparticles, such as TiO 2 , SiO 2 and Fe 2 O 3 [30,37,38]. Other experimental and modeling studies have revealed that the injection of modified brine during the EOR process could desorb asphaltene molecules and other polar components of crude oil from the mineral surfaces and alter the wettability of the pore wall to less oil wet, resulting in improved oil recovery [7,[39][40][41][42]. Ligthelm et al showed that a decrease in salinity increased the expansion of the diffuse double layer between the rock and oil interfaces, facilitating the release of organic materials [11].…”
Section: Introductionmentioning
confidence: 99%